Whose health, whose care, whose say? Some comments on public involvement in new NHS commissioning arrangements - Martin, Graham P. (Routledge, 2009)
Recent health policy in England has demanded greater involvement of patients and the public in the commissioning of health and social care services. Public involvement is seen as a means of driving up service quality, reducing health inequalities and achieving value in commissioning decisions. This paper presents a summary and analysis of the forms that public involvement in commissioning are to take, along with empirical analysis from a qualitative study of service-user involvement. It is argued that the diversity of constituencies covered by the notion of ‘public involvement’, and the breadth of aims that public involvement is expected to achieve, require careful disaggregation. Public involvement in commissioning may encompass a variety of interest groups, whose inputs may include population needs assessment, evaluation of service quality, advocacy of the interests of a particular patient group or service, or a combination of all of these. Each of these roles may be legitimate, but there are significant tensions between them. The extent to which the structures for public involvement proposed recognize these possible tensions is arguably limited. Notably, new Local Involvement Networks (LINks), which will feed into commissioning decisions, are set as the arbiters of these different interests, a demanding role which will require considerable skill, tenacity and robustness if it is to be fulfilled effectively.